The roles and functions of the nurses in one-stop crisis centre: a qualitative study - Shan, Chua Woan (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2008)
In response to high incident rate of violence against women, One Stop Crisis Center, OSCC, is established to meet the needs of victims and provide them with appropriate care in the aftermath. The center deals with victims of domestic violence, sexual assault as well as child abuse. This paper is to study the roles and functions of nurses who dealt with victims of abuse/violence in OSCC. A guideline questionnaire is developed for guidance purpose in the interview regarding current levels of knowledge, the skills needed to be mastered, and the obstacles for the achievement of effective crisis intervention as well as the perception of the training needs of the nurses to identify their understanding of their roles and responsibilities in handling the cases of abuse and violence. Each respondent is interviewed in depth to gain the data. The data is collected by recording and writing down manually. Data shows that the OSCC nurses play many roles in handling the case. The nurses manage the victim/survivor and the flow of the case. They interact and collaborate with multiple agencies including physicians, law officer and social worker. They help to prepare the victim/survivor physically and psychologically in routine assessment and evidence collection. The procedures done are documented and they are always standby to be called to testify in the court. Their roles are extended to follow care in the clinic. As a conclusion, the research explores the roles and functions of nurses in OSCC as well as provides useful suggestions for future nursing development and the improvement of the services delivered by other OSCCs in Malaysia.